INFLUENCE OF SYSTEMS ENGINEERING FEATURES OF CELLULAR RADIO COMMUNICATION NETWORK ON ITS ECOLOGICAL SAFETY - V. I. Mordachev; V. M. Kozel (Наука и техника)
Statistical characteristics of electromagnetic radiation power of mobile stations (MS) and influence of its discrete adjustment in cellular networks, using various technologies of multi-station access, on an average level of MS radiated power that determines ecological danger of a cellular radio network are considered in the paper.